PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, EFEKTIVITAS, DAN RISIKO TERHADAP PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) PADA MASYARAKAT KOTA MEDAN - Sonya Enda Natasha S. Pandia; Evi Juita Wailan’An (Universitas Methodist Indonesia, 2023)
This research aims to determine and analyze the influence of perception of ease use, effectiveness, and risk on the adoption of financial technology (Fintech) among the public of Medan city. The sampling method employed in this study is Lemeshow, and a total of 100 respondents were selected as the research sample. The data analysis method used in this research is the Partial Least Square (PLS) method, implemented with SmartPLS 3.2.9 software. The test results show that variables of perception of the use and Risk has a significant impact on Fintech Adoption, while the Effectiveness variable have no affect on use of financial technology.